Managing capital flows: Experiences from Central and Eastern Europe - Jürgen von Hagen; Iulia Siedschlag (Asian Development Bank Institute (ADBI), 2008)
The countries of Central and Eastern Europe went from being largely closed to being largely open to international capital flows. This paper discusses their experience with capital account liberalization and coping with large capital inflows. We start with a discussion of basic economic characteristics and the real convergence achieved so far, and then discuss the pace and sequencing of capital account liberalization and the degree of international financial integration over the past decade. We then analyze trends and patterns of capital inflows in these countries in recent years. These stylized facts are useful for understanding the macroeconomic implications and policy challenges of coping with large capital inflows, which we discuss next. Finally we conclude with policy implications for emerging Asian economies.
Keywords: E44; F36; F41; 330; Kapitalmobilität; Wirtschaftsintegration; Kapitalverkehrspolitik; Kapitalmarktliberalisierung; Ostmitteleuropa; Asien